ANALYSIS OF TRANSFORMATIONAL LEADERSHIP AND WORKENVIRONMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT THE MEDAN BELAWAN DISTRICT OFFICE - Yose Ferry; Mesra B; Elfitra Desy Surya (RADJA PUBLIKA, 2024)
This study aims to analyze the influence of transformational leadership and work environment on employee performance with organizational commitment as an intervening variable at the Medan Belawan District Office. This study uses a quantitative approach with a survey method by distributing questionnaires to 51 employees as respondents. The sample was determined using a purposive sampling technique so that the data obtained is in accordance with the research objectives. The data were analyzed using path analysis techniques to determine the direct and indirect effects between variables. The results of the study indicate that transformational leadership has a positive and significant effect on organizational commitment. The work environment has a positive but insignificant effect on organizational commitment, so its indirect effect on employee performance is also positive but insignificant. Organizational commitment also has a positive and significant effect on employee performance. Thus, organizational commitment acts as an intervening variable that mediates the effect of transformational leadership on employee performance but not the work environment. The results of this study are expected to be input for leaders in improving employee performance through the application of a transformational leadership style, creating a conducive work environment, and strengthening organizational commitment.